ANALYSIS RELATED TO THE APPLICATION OF E-BILLING PAYMENT METHOD AND MANUFACTURE AS CONCERNED TAX DEPOSIT (SSP) MANUAL TOWARDS THE UNDERSTANDING OF TAX MANDATORY - Nur Widyawati; Larasati Larasati; Juli Prastyorini (LPPM of NAROTAMA UNIVERSITY, 2020)
Tax is the biggest source of APBN income in Indonesia. Various payment applications use the e-billing method or manually. A guide for learn about the effect of applying the e-billing payment method and tax payment slip (SSP) to the understanding of taxpayers. This research is quantitative research. Data collection techniques by giving questionnaires to consumers, conduct observations, interviews, and study relevant literature. The sampling technique uses probability sampling so that a sample of 70 from PT. Kartini Patent. The results showed that there was no significant effect between the e-billing payment methods on the understanding of taxpayers, while the positive and significant effect was shown on the method of manual payment of tax payments (SSP) on mandatory understanding. Based on the results of correlation analysis, this study obtained a value of 0.119 or 11.9% which means it has a very low relationship between the independent and dependent variables.